A six-year observational study of 31 children with early-onset scoliosis treated using magnetically controlled growing rods with a minimum follow-up of two years. (September 2018) - Subramanian, T.; Ahmad, A.; Mardare, D. M.; Kieser, D. C.; Mayers, D.; Nnadi, C.
Abstract : Aims: Magnetically controlled growing rod (MCGR) systems use non-invasive spinal lengthening for the surgical treatment of early-onset scoliosis (EOS). The primary aim of this study was to evaluate the performance of these devices in the prevention of progression of the deformity. A secondary aim was to record the rate of complications. Patients and Methods: An observational study of 31 consecutive children with EOS, of whom 15 were male, who were treated between December 2011 and October 2017 was undertaken. Their mean age was 7.7 years (2 to 14). The mean follow-up was 47 months (24 to 69). Distractions were completed using the tailgating technique. The primary outcome measure was correction of the radiographic deformity. Secondary outcomes were growth, functional outcomes and complication rates. Results: The mean Cobb angle was 54° (14° to 91°) preoperatively and 37° (11° to 69°) at the latest follow-up (p < 0.001). The mean thoracic kyphosis (TK) was 45° (10° to 89°) preoperatively and 42° (9° to 84°) at the latest follow-up. The mean T1–S1 height increased from 287 mm (209 to 378) to 338 mm (240 to 427) (p < 0.001) and the mean sagittal balance reduced from 68 mm (-76 to 1470) preoperatively to 18 mm (-32 to 166) at the latest follow-up. The mean coronal balance was 3 mm (-336 to 64) preoperatively and 8 mm (-144 to 64) at the latest follow-up. The mean increase in weight and sitting and standing height at the latest follow-up was 45%, 10% and 15%, respectively. The mean Activity Scale for Kids (ASKp) scores increased in all domains, with only personal care and standing skills being significant at the latest follow-up (p = 0.02, p = 0.03). The improvements in Cobb angle, TK and T1-S1 heights were not related to gender, the aetiology of the EOS, or whether the procedure was primary or conversion from a conventional growing rod system. A total of 21 children developed 23 complications at a rate of 0.23 per patient per year. Seven developed MCGR-specific complications. Complications developed at a mean of 38 months (3 to 67) after the initial surgery and required 22 further procedures. Children who developed a complication were more likely to be younger, have syndromic EOS, and have a single-rod construct (6.9 versus 9.3 years, p = 0.034). Conclusion: The progression of EOS can be controlled using MCGRs allowing growth and improved function. Younger and syndromic children are more likely to develop complications following surgery. Cite this article: Bone Joint J 2018;100-B:1187–1200.